2020
DOI: 10.1111/hsc.12936
|View full text |Cite
|
Sign up to set email alerts
|

‘I want to be with you, but I have MS’: Challenges of interpersonal relationships from the MS patients’ point of view

Abstract: Interpersonal relationships play an important role in adjustment to disease, coping and improving life quality after onset of Multiple sclerosis (MS). However, considering its specific nature, MS has a considerable effect on interpersonal relationships. Thus, this study was conducted to identify and describe effects of disease on interpersonal relationships through investigating lived experiences of patients. In this research, a total of 24 MS patients were selected through purposive sampling from individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
0
10
1
2
Order By: Relevance
“…This method of proactive disclosure has also been reported as a way of "weeding out those who aren't mentally or emotionally equipped to date someone with a disability" [29, p 8]. Also, in the current study, people expressed that having MS did not mean that they had to now change their standards or settle for less, which is in contrast to a similar Iranian study [10].…”
Section: Discussioncontrasting
confidence: 61%
See 4 more Smart Citations
“…This method of proactive disclosure has also been reported as a way of "weeding out those who aren't mentally or emotionally equipped to date someone with a disability" [29, p 8]. Also, in the current study, people expressed that having MS did not mean that they had to now change their standards or settle for less, which is in contrast to a similar Iranian study [10].…”
Section: Discussioncontrasting
confidence: 61%
“…The importance of healthy communication was emphasized to facilitate understanding of the condition and develop strategies to overcome such obstacles. The impact of physical symptoms on relationships is commonly reported [10] and in the current study the understanding between the couple was emphasized as a strategy to facilitate coping with the day-to-day uncertainties. This is especially important considering previous research indicating that people with MS have been found to bring considerable psychological burden into their relationships [36].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations